A case-control study of bloody diarrhoea transmission in the Morifi, Holy Cross, Mohalinyane and Liphiring health centers catchment areas in Lesotho, 2003 - Voyi, Kuku V.V. (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2005.